Correction: Non-linear links between human capital, educational inequality and income inequality, evidence from China. - Mo Xu; Shifeng Chen; Jian Chen; Taiming Zhang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0288966.].